Short-Term Free-Floating Slice Cultures from the Adult Human Brain - Fernandes, Artur; Mendes, Niele Dias; Almeida, Glaucia Maria; Nogueira, Giovanna Orlovski; Machado, Carla de Moraes [UNESP]; Castro Horta-Junior, Jose de Anchieta de [UNESP]; Assirati Junior, Joao Alberto; Garcia-Cairasco, Norberto; Neder, Luciano; Sebollela, Adriano (Journal Of Visualized Experiments, 2019)
Organotypic, or slice cultures, have been widely employed to model aspects of the central nervous system functioning in vitro. Despite the potential of slice cultures in neuroscience, studies using adult nervous tissue to prepare such cultures are still scarce, particularly those from human subjects. The use of adult human tissue to prepare slice cultures is particularly attractive to enhance the understanding of human neuropathologies, as they hold unique properties typical of the mature human brain lacking in slices produced from rodent (usually neonatal) nervous tissue. This protocol describes how to use brain tissue collected from living human donors submitted to resective brain surgery to prepare short-term, free-floating slice cultures. Procedures to maintain and perform biochemical and cell biology assays using these cultures are also presented. Representative results demonstrate that the typical human cortical lamination is preserved in slices after 4 days in vitro (DIV4), with expected presence of the main neural cell types. Moreover, slices at DIV4 undergo robust cell death when challenged with a toxic stimulus (H2O2), indicating the potential of this model to serve as a platform in cell death assays. This method, a simpler and cost-effective alternative to the widely used protocol using membrane inserts, is mainly recommended for running short-term assays aimed to unravel mechanisms of neurodegeneration behind age-associated brain diseases. Finally, although the protocol is devoted to using cortical tissue collected from patients submitted to surgical treatment of pharmacoresistant temporal lobe epilepsy, it is argued that tissue collected from other brain regions/conditions should also be considered as sources to produce similar free-floating slice cultures.
Keywords: Neuroscience; Issue 153; histoculture; neocortex; ex vivo; neurodegeneration; epilepsy; Alzheimer's